2010
DOI: 10.1016/j.devcel.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Minded Links Cell Cycle-Related Kinase to Cilia Assembly and Hedgehog Signal Transduction

Abstract: SUMMARY Recent findings indicate that mammalian Sonic hedgehog (Shh) signal transduction occurs within primary cilia, although the cell biological mechanisms underlying both Shh signaling and ciliogenesis have not been fully elucidated. We show that an uncharacterized TBC domain-containing protein, Broad-minded (Bromi), is required for high-level Shh responses in the mouse neural tube. We find that Bromi controls ciliary morphology and proper Gli2 localization within the cilium. Using a zebrafish model, we fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 69 publications
8
115
1
Order By: Relevance
“…In Chlamydomonas, four different mutated proteins cause abnormally elongated flagella, including LF2 and LF4 kinases that are homologs of vertebrate CCRK and MAK/ICK, respectively (23). We previously showed that Ccrk knockdown in zebrafish results in abnormal ciliogenesis in kidney epithelial cells (24). Similarly, depletion of Ccrk in cultured cells results in elongated cilia (25).…”
Section: Discussionmentioning
confidence: 99%
“…In Chlamydomonas, four different mutated proteins cause abnormally elongated flagella, including LF2 and LF4 kinases that are homologs of vertebrate CCRK and MAK/ICK, respectively (23). We previously showed that Ccrk knockdown in zebrafish results in abnormal ciliogenesis in kidney epithelial cells (24). Similarly, depletion of Ccrk in cultured cells results in elongated cilia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cdc14b morphant larvae did not display a strong body axis curvature as seen in zebrafish cilia mutants (Cao et al, 2010;Omori et al, 2008;Sullivan-Brown et al, 2008;Tsujikawa and Malicki, 2004;Zhao and Malicki, 2007). However, this weaker phenotype has previously been observed when MOs against genes encoding cilia proteins were injected (Ferrante et al, 2009;Hurd et al, 2010;Ko et al, 2010;Tsujikawa and Malicki, 2004). This difference in the phenotypes is probably due to the decreased efficiency of the MOs by this time in development.…”
Section: Characterization Of Cdc14b Functionmentioning
confidence: 64%
“…Loss of MAK in mouse model system result in abnormal long cilia in photoreceptor cells and human genetic studies revealed that mutation in MAK cause retinitis pigmentosa in human (24)(25)(26)(27). CCRK has also been shown that it affects ciliogenesis in zebrafish model system (28). In contrast to Chlamydomonas studies, knockdown of CCRK expression in vertebrate compromises ciliary structure rather than length.…”
Section: Signaling Pathways In Ciliary Length Controlmentioning
confidence: 86%